SCENARIO DESIGN FOR POST-CONFLICT CITIES: EXPERIENCE OF AN INTERNATIONAL STUDENT STUDIO - Pantiukhina, Oleksandra (Theory and practice of design, 2025)
Purpose. The article aims to highlight the experience of a student studio in formulating scenarios for the sustainable recovery of war-damaged Ukrainian cities, which can be tested and implemented within the framework of strategic planning in de-occupied communities. Methodology. The study is based on a qualitative analysis of international and Ukrainian sources dedicated to post-disaster recovery, sustainable urban development, memorialization, and ecological transformation. The main methods include content analysis of scientific literature, reports from international organizations (UNHabitat, OECD, ICOMOS, FEMA), and case studies of damaged city recovery; as well as a comparative analysis of solutions from different countries with potential adaptation to Ukrainian conditions. Results. A comparative analysis of international approaches to post-war reconstruction and revitalization of destroyed territories was conducted, taking into account social, ecological, and spatial aspects. Scientific novelty. For the first time, based on an interdisciplinary analysis of international experience, the key requirements for scenario-based design of post-conflict community recovery have been systematized. Practical relevance. The obtained results can be integrated into the curricula of architectural and urban planning faculties to develop future specialists’ competencies in sustainable design and reconstruction. The proposed approaches can also be used in preparing tasks for the development of community recovery strategies in post-crisis conditions and in comprehensive strategic planning of territorial community development.